HUBUNGAN KELEKATAN ORANGTUA DENGAN KEPERCAYAAN DIRI ANAK USIA 4-5 TAHUN DI TK SE-KECAMATAN SINDANG JAYA KABUPATEN TANGERANG-BANTEN - Irma Lailah Sari; Luluk Asmawati; Laily Rosidah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2020)
Early childhood confidence is a positive attitude that makes children brave to appear in the surrounding environment. Parents are the first environment known to children, children who have secure attachment to parents will have good socialization skills, are easier to be friendly, have healthy relationships, and are adaptable to the social environment because they believe the environment that children live in provides comfort and security. The purpose of this study aims to determine whether or not there is a significant relationship between the attachment of parents to the self-confidence of children aged 4-5 years in Kindergarten in Sindang Jaya District, Tangerang-Banten Regency. The research method uses a correlation analysis method with a quantitative approach with a sample of 61 children and their parents. Sampling uses a purposive sampling technique with certain criteria. The test results of the correlation coefficient of parental attachment with 4-5 years of children's confidence show a figure of 0.532, which means having a moderate relationship because it is in the interval of the category 0.40-0.599. This means that if parental attachments relate well to the self-confidence of children in the medium category. From the results of the t test it is also known that the tcount of parent attachment variable is 4.832> 2.001 and the sig value is 0.000 <0.05 which means tcount> ttable or sig <a value, there is a significant relationship between the two variables, namely there is a significant relationship between attachment of parents to the self-confidence of children aged 4-5 years.